Uma análise da decomposição da pobreza regional no Brasil (2005-2015) - Forte, Francisco Wagner Bizerril (2021)
This study verifies the trend of the regional poverty indexes and decomposes the variation of poverty by its main determinants: growth and redistribution. Thus, a Shapley decomposition was used through the methodology proposed by Shorrocks (1999), with data from the National Household Sample Survey (PNAD) from 2005 to 2015. The measurement of poverty is treated based on the Foster family of indices Greer-Thorbecke (FGT), using the poverty line proposed by Rocha (1997), a type based on a basket of minimum daily caloric consumption. Among the main results obtained, there is a decreasing trend in the regional poverty indexes, both for those surveyed and for children and young people in the analyzed period. Evidence from the analysis of the decomposition of variation in poverty into a component of growth and redistribution points out that both the growth of average income and the redistribution of income was common to poverty, but in different magnitudes, indicating that the deterioration of income inequality contributes to the aggravation of Brazilian regional poverty.